Pengaruh Faktor Internal dan Eksternal Terhadap Ketidaktepatan Waktu Penyampaian Laporan Keuangan Auditan Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Siti Muarifah; Ridwan Jaza'i (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
One of the most important measures of accountability and transparency in public firms is the promptness with which audited financial reports are submitted. Listed businesses on the Indonesia Stock Exchange (IDX) continue to often experience financial reporting delays, especially in recent years. This can result in information asymmetry and worse market efficiency. Thus, the purpose of this study is to examine how internal and external factors affect the tardiness of audited financial report submissions among firms listed on the IDX between 2024 and 2025. This study uses a descriptive-verificative strategy in conjunction with a quantitative approach. Purposive sampling was used to pick samples based on corporations that regularly published audited financial reports, yielding 77 suitable firms. The official IDX website's yearly reports and publishing dates provided secondary data. Data analysis was conducted using multiple linear regression with SPSS version26. The findings show that all independent factors have a considerable simultaneous impact on the tardiness of audited financial report submissions. Related party connections and PAF modifications significantly and favourably affect reporting delays, whereas profitability, audit committee turnover, and audit opinions show no significant effect. These findings reveal that structural and technical factors—such as inter-entity complexity and auditor rotation—are more influential in causing reporting delays than financial performance factors. In conclusion, improving corporate governance effectiveness, strengthening digital reporting systems, and implementing efficient auditor rotation planning are essential to minimize reporting delays and enhance transparency in Indonesia’s capital market.